The removal of the Amazigh language from the experience of the ‘pioneer schools’ project in Morocco : what impact on teaching practice, its promotion and its development? - Mariem SADIQI; Ahmed BOUOUD (African Scientific Journal, 2025)
Abstract : It's essential to stress that the integration of the Amazigh language into the public education system is a hotly debated issue, emerging in Morocco and other North African countries where the language is spoken. This idiom, also known as Berber, has a rich history and has been deeply rooted in the culture and identity of the peoples of North Africa for thousands of years. It's worth pointing out that in Morocco, where the Amazigh language is widely spoken, it was granted official language status in 2011 and enjoys greater recognition in the media and government institutions. It's worth noting that the 2023/2024 school year will be marked by the reform of “pioneer schools”, a project aimed at improving the quality of teaching and learning. However, our research aims to discover how the power of a reform within an education system can banish and discriminate against a language that has just been formalized and taught. What impact will this project have on the teaching of the Amazigh language? And above all, what role will Amazigh language teachers play during the TARL period (we'll expand on this subject in the next few lines) when the subjects to be supported don't go beyond Arabic, French and mathematics? This project comes after a long struggle and relentless efforts to make the Amazigh language official and teachable, but instead of moving forward, the pioneering school is sidelining the language, which will disrupt its promotion and hinder its development. Anchored in a linguistic epistemological framework, we have opted for a qualitative approach, with the aim of interpreting rather than simply explaining the facts observed. By means of an empirical-deductive approach, we aim to understand how a large-scale reform can neglect a language freshly introduced to the education system, and drive it out of its accounts will have detrimental repercussions on the teaching-learning of the Amazigh language, and on the motivation and performance of teachers and their learners, as this study will illustrate. Resolutions must be put in place to encourage the evolution of Amazigh language teaching and learning. Key words: pioneer schools, diglossia, learning, language management, sociodidactics